2019
DOI: 10.1017/dmp.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Affordable Housing in Disasters: Western Iran Earthquake in 2017

Abstract: In November 2017, a disruptive earthquake occurred in Western Iran. After the major earthquake in Kermanshah, most affordable buildings such as a hospital in Islamabad and a dozen schools were destroyed. According to experts, a dangerous location (construction on the fault), poor quality of concrete, inappropriate connection of the facade to the structure, the use of undesirable construction materials, and low quality of non-structural components are considered as the main reasons for these damages. Regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In 2016, about 54.5% of the global population occupied urban areas and big cities; health units are very important, and their functionality is vital during emergency response [27]. In November 2017, a powerful earthquake destroyed houses, schools and hospitals (at least 40% destroyed) in Iran near the fault line; the quality of the material used and the lack of repairs aggravated the vulnerability [54]. The probabilistic earthquake performance based on performance-based earthquake engineering (PBEE) methodology can be used for community resilience [55].…”
Section: Framework For Building Performance In the Assessment Of Comm...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, about 54.5% of the global population occupied urban areas and big cities; health units are very important, and their functionality is vital during emergency response [27]. In November 2017, a powerful earthquake destroyed houses, schools and hospitals (at least 40% destroyed) in Iran near the fault line; the quality of the material used and the lack of repairs aggravated the vulnerability [54]. The probabilistic earthquake performance based on performance-based earthquake engineering (PBEE) methodology can be used for community resilience [55].…”
Section: Framework For Building Performance In the Assessment Of Comm...mentioning
confidence: 99%
“…Furtado et al, 2021 [98] highlighted that in important buildings like school buildings, past earthquake planning is needed to take into account resilience. Heidari et al, 2020 [54] showed that governments should formulate useful policies to reduce vulnerability and increase resilience. The research of Pesaralanka et al, 2023 [56] is limited to linear analysis only; the damages of NSEs and EAL need to be researched further.…”
Section: Research Gapmentioning
confidence: 99%
“…In 2016, about 54.5% of the global population occupied urban areas and big cities; health units are very important and their functionality is vital during emergency response [58]. In November 2017, a powerful earthquake destroyed houses, schools and hospitals (at least 40% destroyed) in Iran near the fault line; the quality of material used and the lack of repairs aggravated the vulnerability [59].…”
Section: Framework For Building Performance In the Assessment Of Comm...mentioning
confidence: 99%